Discontinuation of afterload-reducing drugs decreases left ventricular outflow tract obstruction in hypertrophic obstructive cardiomyopathy - Derda, Anselm A.; Abelmann, Malin; Sonnenschein, Kristina; Sieweke, Jan-Thorben; Bavendiek, Udo; Bauersachs, Johann; Thum, Thomas; Berliner, Dominik (Frontiers in Cardiovascular Medicine, 2024)
Background Hypertrophic cardiomyopathy (HCM), the most common genetic heart disease, is classified into hypertrophic non-obstructive and hypertrophic obstructive cardiomyopathy (HOCM). Patients with HOCM and coexisting heart failure or arterial hypertension are often prescribed afterload-reducing drugs. Although recommended in current guidelines, data on the direct effect of discontinuing afterload-reducing medication are scarce. This study aims to demonstrate the benefit of discontinuing afterload-reducing medication in HOCM patients. Methods This monocentric retrospective analysis included 24 patients with HOCM with afterload-reducing medication, including angiotensin-converting enzyme inhibitors, angiotensin-1 receptor blocker and dihydropyridine-calcium channel blocker, at their first outpatient visit. Effects of discontinuing this medication on LVOTO were examined compared to patients with persistent use despite medical advice. Results 16 patients discontinued their afterload-reducing drugs, resulting in a significant decrease in median LVOT gradient from 86.5 [60.5–109.3] mmHg to 61.5 [28.3–97.50] mmHg (p = 0.0004). In 6 patients, beta-blocker therapy was initiated simultaneously, or the dose was increased. Regardless, LVOT gradient reduction was also significant in the remaining 10 patients (p = 0.001). The gradient was not changed significantly in the 8 patients continuing their afterload-reducing medication. Conclusions Discontinuation of afterload-reducing drugs significantly decreases LVOTO. Our study underscores the significance of abstaining from afterload-reducing drugs in HOCM patients, particularly in patients with concomitant hypertension or heart failure. According to recently published European guidelines, HOCM patients should preferably be treated with beta-blockers or non-dihydropyridine-calcium channel blockers.